An Evaluation of Combustion Kinetics for the Synthesis Reaction of the Reinforcing Phase During Casting Phase During Casting - Wiktor, Tomasz; Sobula, Sebastian; Burbelko, Andryi; Ptasznik, Michał (Journal of Casting & Materials Engineering, 2020)
The computer modeling of the solidification process in castings with local composite reinforcement (LCR) obtained as a result of in situ reactions of self-propagating high temperature synthesis (SHS) is difficult due to limited data on the thermo-physical parameters of exothermic effects and the kinetics of the synthesis reaction. In the present study, Hadfield cast steel casting was manufactured with LCR containing titanium carbide particles obtained in situ by the SHS method. Reaction kinetics of titanium carbide synthesis in the composite casting were determined on the basis of temperature measurements in the area of LCR during the process. For the estimation of the reaction, the Fourier Thermal Analysis method was used. The paper presents the results of temperature measurement and the results of the calculation of SHS reaction kinetics. It was found that the reaction time under the conditions of the analyzed casting is below 3 s.